The Application of âThe Mystery Guest Gameâ to enhance the Students English Verbal Communication of Grade X-1 of SMA Pabelan in 2010/2011 - Sudiyatno, Agus (Register Journal, 2011)
This classroom action research was carried out due to the studentsâ low achievement in the verbal performance.Â  There was a question whether the application of âThe Mystery Guest Gameâ could increase the studentsâ skill in communication. The purpose of this research was (1) to increase the studentsâ skill in their verbal communication, (2) to increase their interests in learning the language. After having finished the research for 2 cycles, the result was gained as follows. At the cycle I, the studentsâ performance showed 41 sentences during 21 minutes. It means in 21 minutes students could ask 41 recorded questions during the class observation.Â  The rate is 1.95. At the second week the rate showed 2.58 which show an increase of 32%. At the third week, the rate shows an increase of 83% compared to the second performance. At the cycle II, the increase of studentâs performance showed 15% or of 5.45 compared to the third week of the cycle I. The studentsâ performance at the second week increases to 6.95 or 27.6%. At the third week the students performance increase to 160 sentences or 4.60% compared to the second week. The studentsâ responses based on the questionnaires show that 85% students were interested in the teaching and the game is the main reason. The percentage of performance was 77%. Those evidences showed that âThe Mystery Guest Gameâ increased studentsâ interest in English during the teaching game.Â  keywords; âThe Mystery Guest Gameâ; verbal;Â  enthusiasm